2019
DOI: 10.5430/ijfr.v11n1p60
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Company Characteristics of Firm Values: Profitability as Intervening Variables

Abstract: This study aims to analyze the factors that influence company value (PBV) in consumer goods companies listed on the Indonesia Stock Exchange in 2014-2018. The independent variables used in the study are capital structure (DER), company size (SIZE), liquidity (CR) with profitability (ROE) as an intervening variable.The population used in this study is all companies engaged in the consumer goods sector listed on the Indonesia Stock Exchange in 2014-2018. Sampling in this study used purposive sampling which resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
42
4
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 7 publications
12
42
4
15
Order By: Relevance
“…The study results align with the signal theory, which states that companies always give good performance signals to outsiders, especially investors. These results are in line with the results of research conducted by Chabachib et al (2020), Antoro et al (2020), Natsir & Yusbardini (2020), Tumanggor (2019), Burhanuddin & Taufik (2019), Sahbany et al (2019).…”
Section: Sobel Testsupporting
confidence: 90%
“…The study results align with the signal theory, which states that companies always give good performance signals to outsiders, especially investors. These results are in line with the results of research conducted by Chabachib et al (2020), Antoro et al (2020), Natsir & Yusbardini (2020), Tumanggor (2019), Burhanuddin & Taufik (2019), Sahbany et al (2019).…”
Section: Sobel Testsupporting
confidence: 90%
“…The result of the hypothesis testing obtained that profitability could mediate influence between capital structure and firm value in the manufacturing sector. The result of this study is not in line with the studies by (Chabachib et al, 2020). Consequently, the amount of the company's debt will directly affect firm value through the involvement of earnings generated by the company during a certain period.…”
Section: The Influence Of Capital Structure On Firm Value Through Profitabilitycontrasting
confidence: 84%
“…The increased stock price will influence firm value. A study by (Chabachib et al, 2020) stated that profitability did not influence the correlation between capital structure and firm value.…”
Section: Profitabilitymentioning
confidence: 97%
“…The Board of Commissioner (BOC) represents the internal mechanism of GCG to control and oversee management behavior in managing the company so that it can align the interests of shareholders and company managers (Jensen & Meckling, 1976). Chabachib, Hersugondo, Ardiana, & Pamungkas(2019) said that board of commissioner is the core of GCG which is tasked with ensuring company strategy and supervising managers in managing the company, so that BOC has a very strong influence on firm value. In addition, Yacob, Jambi, Rahayu, & Jakarta(2019)andCiftci et al, (2019) also found similar results that the board of commissioners had a positive influence on firm value.…”
Section: Borad Of Commissioner and Firm Valuementioning
confidence: 99%